Novel pathogenic COX20 variants causing dysarthria, ataxia, and sensory neuropathy. Issue 1 (9th November 2018) - Otero, Maria G.; Tiongson, Emmanuelle; Diaz, Frank; Haude, Katrina; Panzer, Karin; Collier, Ashley; Kim, Jaemin; Adams, David; Tifft, Cynthia J.; Cui, Hong; Millian Zamora, Francisca; Au, Margaret G.; et al.
Abstract: COX20/FAM36A encodes a mitochondrial complex IV assembly factor important for COX2 activation. Only one homozygous COX20 missense mutation has been previously described in two separate consanguineous families. We report four subjects with features that include childhood hypotonia, areflexia, ataxia, dysarthria, dystonia, and sensory neuropathy. Exome sequencing in all four subjects identified the same novel COX20 variants. One variant affected the splice donor site of intron‐one (c.41A>G), while the other variant (c.157+3G>C) affected the splice donor site of intron‐two. cDNA and protein analysis indicated that no full‐length cDNA or protein was generated. These subjects expand the phenotype associated with COX20 deficiency.